2014
DOI: 10.1002/app.40620
|View full text |Cite
|
Sign up to set email alerts
|

Inherently adaptive polymer nanocomposites

Abstract: A new class of inherently adaptive polymer nanocomposites is developed where stress‐enabled redox reactions are used in the context of a solid polymer electrolyte to form deposits which render mechanical strengthening effects. Experimental investigations were conducted to provide insight into this self‐adaptation phenomenon. Results of tests conducted on bolted composite joints demonstrated the occurrence of this self‐adaptation phenomenon. Experiments were also performed on cracked composite specimens where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The adaptive feedback controller was designed and implemented first on a newly developed model of an electrolytic system to regulate the process. The model is based on previous experimental work [6,38] which proposed an electromechanical material system, whose intrinsic self-healing mechanism is based on a piezo-electrolytic drive. This system suffers from an inherent non-linear deadzone which limits the performance of selfhealing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adaptive feedback controller was designed and implemented first on a newly developed model of an electrolytic system to regulate the process. The model is based on previous experimental work [6,38] which proposed an electromechanical material system, whose intrinsic self-healing mechanism is based on a piezo-electrolytic drive. This system suffers from an inherent non-linear deadzone which limits the performance of selfhealing.…”
Section: Resultsmentioning
confidence: 99%
“…An adaptive feedback controller in figure 6(b) is designed to regulate the self-healing process by overcoming the inherent deadzone and ensuring a proper match between healing and damage rate. The system model (21) is modified by adding a feedback control law U (t) to give Equation (38).Q…”
Section: Case Ii: Piezo-electrolytic Process Regulated By a Feedback mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental work has shown that the macro properties of interest are recovered by the self-healing process adopted here. 34,35 However, details on how and to what extent the original macro material properties can be recovered for different host structures, would require further experimental investigation with the potential self-healing processes. Complete recovery of the macro material properties is assumed here, since the actual recovered values are not known and its adoption does not affect the investigation of the general concept, which is the main focus in this work.…”
Section: Integration Of System Model and Control With Fddmentioning
confidence: 99%
“…To achieve a sh (t h )=a est (t f ),( 51)m u s t hold. The fault monitoring index in (35) is redefined as (52) during self-healing. The second row of (46)i sa l s or e s e t to zero.…”
Section: Integration Of System Model and Control With Fddmentioning
confidence: 99%